2017
DOI: 10.3892/ijmm.2017.3212
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of vascular smooth muscle cells under inflammation is regulated by NF-κB p65/microRNA-17/RB pathway activation

Abstract: Inflammation and excessive proliferation of vascular smooth muscle cells (VSMCs) have key roles in various vascular disorders, including restenosis, atherosclerosis and pulmonary artery hypertension. However, the underlying mechanism remains unclear. The present study investigated the role of nuclear factor-κB (NF-κB) and microRNA (miRNA) in the regulation of VSMC proliferation under inflammatory conditions. It was demonstrated that miR-17 stimulated the proliferation of VSMCs, enhanced cell cycle G1/S transit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 38 publications
4
43
0
Order By: Relevance
“…Higher RDW is frequently driven by occult inflammation, an occult modulator of miRNA expressions in vascular cells. 10 These evidences support the notion that they modify circulating miR-125b levels through altering their expressions in different tissues (Figure 2). miR-125b have been repeatedly shown to be pathogenetically important in vascular remodeling during CKD, especially VC.…”
Section: Dear Editorsupporting
confidence: 79%
“…Higher RDW is frequently driven by occult inflammation, an occult modulator of miRNA expressions in vascular cells. 10 These evidences support the notion that they modify circulating miR-125b levels through altering their expressions in different tissues (Figure 2). miR-125b have been repeatedly shown to be pathogenetically important in vascular remodeling during CKD, especially VC.…”
Section: Dear Editorsupporting
confidence: 79%
“…According to early reports, P65, the central component of NF-КB pathway, had been suggested to act as a transcription factor in various kinds of diseases [ 30 33 ]. Dong Yang et al identified that P65 induced miR-17 transcription by binding its promoter elements to regulate proliferation of vascular smooth muscle cells under inflammation [ 34 ]. Rezapour S et al reported that P65 was constitutively activated in colorectal cancer [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…21 MiR-26a can contribute to the PDGF-BB-triggered phenotypic switch of vascular smooth muscle cells by inhibiting Smad1. 22 MiR-362-3p can restrain vascular smooth muscle cell proliferation by targeting ADAMTS1 in atherosclerosis. 23 It has been indicated that miR-370 is involved in coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%